Concentration of pistachio hull extract antioxidants using membrane separation and reduction of membrane fouling during process. Issue 6 (6th August 2018) - Seifzadeh, Negin; Sahari, Mohammad Ali; Barzegar, Mohsen; Ahmadi Gavlighi, Hasan
Abstract: The purpose of this study was to concentrate the polyphenolic compounds in pistachio hull extract as a rich source of natural antioxidants using the membrane process and the reduction of membrane fouling during the process. After the optimization of the membrane performance includes chamber pressure and stirring rate by monitoring flux and membrane fouling, pectinase and tannase enzymes were compared in order to reduce fouling. Pectinase showed a better potential in decreasing membranous fouling. Enzyme concentration was optimized, and treatment with 17.4 (U) was selected. The permeate obtained from optimized membrane condition and enzyme level treatment was enriched in total phenol (120.31 ± 0.35 mgGAE/g) and flavonoid (34.54 ± 0.09 mgCE/g), while the amount of anthocyanin was not remarkable. Abstract : Owing to the importance of production and introducing a natural antioxidant as a substitute for chemicals, the ultrafiltration system can be effective in concentrating polyphenols in the pistachio hull aqueous extract up to 21.16%; on the other hand, using 17.4 (U) pectinase enzyme can reduce membrane fouling up to 44.8%.